Holding On to the Past and the Fallacy of the Traditional Family in Anne Tyler’s Dinner at the Homesick Restaurant - Salazar, Anthony (International Journal of English Literature and Social Sciences (IJELS), 2019)
While many writers during the mid-twentieth-century focused on the ideality of the traditional family, Anne Tyler, in Dinner at the Homesick Restaurant, challenged such ideality by focusing on a family in which the father abandons his role as the breadwinner. Because the mother must then fulfill the duties assigned to the father and mother, the children grow up reflecting negatively on their childhood. The siblings’ perceptions of the past, however, stem from an inability to achieve the traditional family. This essay therefore examines the characters’ negotiations with the past and exposes the fallacy of the perfect family, for, as Anne Tyler implies, such family structure is not achievable.